A Study On Technical Analysis Of Selected FMCG Scripts With Reference To Annamalai Capital Services (P) Ltd., Coimbatore City - et. al., Mehta Vani Joghee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
“Risk comes from not knowing what you’re doing.” – Warren Buffett The study in focus mainly concentrates on understanding the pricing patterns drawn by top five firms from Fast Moving Consumer Goods in National Stock Exchange using Technical Analysis. The price movements of the subjected companies are being observed by the implication of various technical indicators and charts over a pre-determined period. Through the study we could watch the turning points i.e. Trend creation which helps us to determine the buy and sell signals. This study also allows us to spot the resistance and support level of the underlying firm alongside identifying the better performing FMCG Company while comparing to that of others based on their price fluctuation